Virtual Classroom Design for the Deaf Based on Cloud Computing - Livia Maukar (JR Education, 2021)
The development of information technology is growing rapidly, giving rise to various innovations that also change human behavior, especially in interaction and communication. Cloud Computing is a hot topic for today's technological developments. Persons with disabilities are people who have physical, mental, intellectual, or sensory limitations for a long period of time (Law No. 19 of 2011). Deaf and speech impaired people need signs or alarms that are visual in nature, either as picture symbols or in the form of lights. Currently, virtual classes have begun to be used as learning alternatives. Virtual class (virtual class) is a class based on the web, where teachers and students can interact anytime and anywhere without being limited by space and time. The purpose of making this design is so that the learning process for the deaf can run well. The method used is a collaborative Design Thinking method that collects many ideas from scientific disciplines to obtain a solution. Cloud computing can be used as a technological instrument that facilitates the construction of a good application for students with special needs. With the design thinking method, good applications can be produced and are able to produce a good learning process for students with special needs.